Pricing structures for solutions: an exploratory study within the oil and gas industry. Issue 22 (17th November 2019) - Frandsen, Thomas; Boa, Sofie Østergaard; Raja, Jawwad Z.
Abstract : A growing number of companies have begun to realise the potential for differentiating their product offerings by integrating services to provide customised solutions. Although there is now an extensive and growing literature on this trend, researchers have only recently begun to consider the pricing structures for such solutions. To address this shortcoming, the present study adopts an exploratory case-based approach to investigate a buyer (drilling contractor) and two suppliers of offshore capital equipment, each of whom provides condition-based maintenance solutions for offshore drilling units in the upstream oil and gas industry. The findings of the study identify a number of underlying mechanisms for solution offerings (i.e. innovativeness, benchmarking alternatives, measurability, replicability and operational risk) that are important considerations in the process of determining appropriate pricing structures based on the buyer's business model, procurement practices and maintenance strategy vis-à-vis the supplier's capabilities and the buyer–supplier relationship. The present study contributes to the literature by providing empirical evidence on and insight into the complexity of determining the pricing structure for solution offerings from the perspective of the supplier as well as the buyer.